A study of active monsoon over India using satellite radiation data - SRINIVASAN, V. (MAUSAM, 1971)
Tiros VH radiation data in the 8-12 micron channel for the period 5-8 July 1963 has been analysed. This was a period of good monsoon activity in the Peninsula and central India, The I.R. analysis is compared with surface synoptic and upper air charts. The results indicate that the general height of tops of monsoon clouds is about 7.8 km and these clouds presumably do not extend much into the upper tropospheric easterlies. However, in the areas of localised heavy monsoon activity. the clouds extend at least as high as 12 km. The average size of such thick cloud clusters is of the order of 3 to 5 degrees of Lat/Long, across and !n some cases even more.